Q. 135.0( 1 Vote )

# For any Δ ABC sho

Answer :

**Note:** In any ΔABC we define ‘a’ as the length of the side opposite to ∠A, ‘b’ as the length of the side opposite to ∠B and ‘c’ as the length of the side opposite to ∠C.

**The key** **point to solve the problem:**

The idea of cosine formula in ΔABC

• Cos A =

• Cos B =

• Cos C =

As we have to prove:

= (a+b+c)^{2}

The form required to prove contains similar terms as present in cosine formula.

∴ Cosine formula is the perfect tool for solving the problem.

As we see the expression has bc, ac and ab terms so we will apply the formula of cos A, cos B, and cos C all.

As cos A =

⇒ 2bc cos A = b^{2} + c^{2} – a^{2}

We need (b + c )^{2} in our proof so adding 2bc both sides –

∴ 2bc + 2bc cos A = b^{2} + c^{2} +2bc – a^{2}

⇒ 2bc ( 1 + cos A) = (b + c)^{2} - a^{2}

∵ 1 + cos A = 2cos^{2} (A / 2) { using multiple angle formulae }

∴

⇒

⇒ ….eqn 1

Similarly,

….eqn 2

And,

….eqn 3

Adding equation 1, 2 and 3 we have –

**…Hence proved**

Rate this question :

In a ΔABC, if <spRD Sharma - Mathematics

For any Δ ABC shoRD Sharma - Mathematics

Two ships leave aRD Sharma - Mathematics

In a Δ ABC cos<suRD Sharma - Mathematics

In any Δ ABC, <spRD Sharma - Mathematics

In a Δ ABC cos<suRD Sharma - Mathematics

Two ships leave aRD Sharma - Mathematics

In any Δ ABC, <spRD Sharma - Mathematics

For any Δ ABC shoRD Sharma - Mathematics

For any Δ ABC shoRD Sharma - Mathematics